The Role of Islamic Education Teachers in the Development of Students’s Islamic Character at SD IT Al-Furqon - Luthfi Febriani; Nenden Munawaroh (Al-Ulum: Jurnal Pendidikan Islam, 2026)
Investigates implementation of Islamic Religious Education, condition of students’ Islamic character, and teachers’ strategies in fostering these values at SD IT Al-Furqon. Qualitative approach was employed, with data collected through interviews, observations, also document analysis. Participants included PAI teachers as key informants, supported by school principal and students. Reveal that PAI learning at SD IT Al-Furqon is conducted systematically through integration of interactive lectures, discussions, memorization, also habituation of religious values in daily school activities. Students’ Islamic character is generally categorized as good, particularly in terms of discipline, politeness, and responsibility, although challenges such as behavioral inconsistency and environmental influences remain. PAI teachers play a crucial role in character development by integrating Islamic values into both instructional and non-instructional activities, including routine religious programs. Collaboration between teachers and parents strengthens students’ moral development. Contributes to literature by highlighting Islamic character education strategies based on religious habituation and teacher role modeling within context of an integrated Islamic elementary school.